2016
DOI: 10.1007/s11255-016-1335-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum levels and dietary intake of isoflavone, and the novel bacterium Slackia sp. strain NATTS with the risk of prostate cancer: a case–control study among Japanese men

Abstract: Our study findings suggest that high serum levels of genistein, daidzein, and glycitein are significantly associated with a decreased risk of prostate cancer among Japanese men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Of the 2531 articles that were screened by abstract, 39 articles were found to contain potentially relevant information and were evaluated by full text review. Upon reviewing the full text articles for the aforementioned inclusion criteria, 30 articles were included in the final analysis [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Of these 30 articles, 24 [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 46 , 47 , 48 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 2531 articles that were screened by abstract, 39 articles were found to contain potentially relevant information and were evaluated by full text review. Upon reviewing the full text articles for the aforementioned inclusion criteria, 30 articles were included in the final analysis [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Of these 30 articles, 24 [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 46 , 47 , 48 ,…”
Section: Resultsmentioning
confidence: 99%
“…Of the 30 articles included for analysis, fifteen [ 28 , 29 , 30 , 32 , 34 , 37 , 38 , 39 , 41 , 42 , 47 , 48 , 49 , 52 , 56 ] articles were case-control studies, eight [ 27 , 31 , 33 , 36 , 43 , 45 , 46 , 53 ] articles were cohort studies, and seven [ 35 , 40 , 44 , 50 , 51 , 54 , 55 ] articles were nested case-control studies (NCC). The total number of study participants included was 266,699, and the total number of PCa cases reported was 21,612.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of Eubacterium and Clostridium_IV have been revealed to be major butyrate-producing bacteria in the human colon 51 . Members of Slackia have been shown to exhibit a high adhesion capacity to human Caco-2 cells 52 and to also be involved in the pathogenesis of prostate cancer 53 . However, little information is presently available on the cell-wall components and metabolites of the gut bacteria that belong to these clades.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating epidemiological evidence has highlighted a geographical basis for PCa incidence, and isoflavone consumption may be related to this phenomenon. Indeed, PCa is more common in Western than Asian populations, and several trials have demonstrated that soy derivatives genistein and daidzein can prevent the development and progression of this tumor in Japanese and Chinese men [293][294][295][296]. On the contrary, the data collected in European patients are still contradictory.…”
Section: Clinical Impactmentioning
confidence: 99%